ISOLATION AND IDENTIFICATION OF NATURALLY OCCURRING LARVICIDAL COMPOUND ISOLATED FROM ZINGIBER ZERUMBET (L).J.E. SMITH. - Murini, Tri; Wahyuningsih, Mae Sri Hartati; T SATOTO, TRI BASKORO; Fudholi, Achmad; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A naturally occurring larvicidal compound is an alternative to eradication of Aedes aegypti larvae. This compound is toxic to larvae but relatively safe for human. Rhizome of Lempuyang gajah (Zingiber zerumbet (L.) J. E. Smith) has been used traditionally to prevent mosquito bites. An initial study indicated that petroleum ether (PE) soluble fraction of the methanol (MeOH) extract of Z. zerumbet was toxic against larvae lethal concentration (LC50), 67.01±2.35 versus 153.57±4.01 ppm (MeOH ext.). Therefore, this study aimed to isolate and identify the compounds with larvicidal activity from Z. zerumbet rhizome. Methods: The PE soluble (PE-soluble) fraction was subjected to a bioassay-guided fractionation and isolation method to obtain four (4) fractions (I-IV). Two compounds (1 and 2) were isolated from Fraction I that was the most active compared to other fractions (II-IV). Compound 1 turned out to be more active than compound 2; therefore, compound 1 was then identified by means of spectroscopic data. Results: Based on the LC50 values, compound 1 was more active than compound 2 (LC50, 41.75±0.05 and LC90, 57.66±3.37 [1] versus 1122.27±1.80 and 1875.69±1.35 ppm [2]), and compound 1 was identified as Zerumbone. Conclusion: Zerumbone was the main active compound; in the future, this compound can be formulated as a standardized preparation based on the content.